ADVANCING SUSTAINABLE AGRICULTURE IN VIETNAM THROUGH BIOTECHNOLOGY AND ARTIFICIAL INTELLIGENCE - Phan Thi Huyen (HUIT Journal of Science, 2025)
Vietnamese agriculture is increasingly vulnerable to the impacts of climate change, which has led to more frequent and severe crop diseases, making it challenging for farmers to sustain productivity. In response, the heavy use of chemical fertilizers and pesticides has resulted in soil degradation, raised serious food safety, public health concerns, and environmental problems. Addressing these issues requires a shift toward more sustainable agricultural practices that can support both productivity and ecological resilience. This paper examines how Vietnam can move toward a more sustainable agricultural model by integrating biotechnology and artificial intelligence (AI). Biotechnology provides innovative solutions that reduce dependence on harmful chemicals while improving soil quality and crop health. When integrated with AI, it can enhance the development of biofertilizers, biopesticides, and high-yield, climate-resilient crop varieties with greater precision and efficiency. Drawing on global case studies, this research highlights how Vietnam can adopt these technologies to tackle its specific agricultural challenges. The adoption of biotechnology and AI-driven solutions has the potential to transform Vietnamese agriculture into a high-tech, environmentally friendly system that balances productivity with sustainability. However, realizing this transformation requires substantial investment in biotech research and infrastructure, the development of a skilled workforce, and the establishment of clear, comprehensive regulatory frameworks for innovations. By learning from international experiences and adapting them to local conditions, Vietnam can build a resilient and sustainable agricultural future that ensures both food security and environmental protection in the face of climate change.